EKSPLORASI MIMIK WAJAH DALAM KARYA LUKIS SUREALIS - Frans Nanda Soferry; Mediagus .; Abd. Hafiz (Universitas Negeri Padang, 2012)
Abstract The aim of this final project is to explore the face expression and visualize some kind those ekspression in the sureal way. Face expression is the way to express the feeling, everything that you felt in your heart will be reflect automatically in your face. The view of face exploratian will be shown in the painting with the title : 1), “Eksplorasi” 2), “Bomb Waktu” 3), “Meleleh” 4), “Clown” 5), “Ganti topeng” 6), “Histeris” 7), “Bosan” 8), “Uuugghhh…” 9), “Terbuai Dalam Hijau” dan 10), “Solusi”. Further more, the writter will give priority to snapshot about face expression of human such as, anger, smile, cry, affraid, pain, and camouflage the feeling and it will show in sureal painting with confront the expression way and explore the possibility of thing without remove the real characteristic of face expression. Kata kunci : Eksplorasi, Mimik, Wajah, Surealis